Analisis Tingkat Kepuasan Penumpang terhadap Kualitas Pelayanan AKAP Bus Rute Gorontalo-Kotamobagu pada Terminal Dungingi - Wahyu Hidayat; Yulianti Kadir; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Public transportation plays an important role in supporting community mobility and economic activities. One of the transportation modes that is still widely used by the public is the Intercity and Interprovincial Bus (AKAP). The success of bus transportation services is determined not only by the operator's ability to provide vehicles but also by the quality of services delivered to passengers. Passenger satisfaction is an important indicator in evaluating transportation service quality because it is closely related to customer loyalty and service sustainability. This study aims to analyze passenger satisfaction with the service quality of AKAP buses operating on the Gorontalo–Kotamobagu route at Dungingi Terminal and to identify service dimensions that require improvement. This research employed a quantitative approach using a survey method involving 65 respondents selected through purposive sampling. The research instrument was developed based on the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using the Customer Satisfaction Index (CSI) and GAP analysis to measure the discrepancy between passengers’ perceptions and expectations. The results indicate that all research instruments were valid and reliable, with Cronbach’s Alpha values greater than 0.60. The GAP analysis revealed negative values across all service dimensions, indicating that the quality of service has not fully met passenger expectations. The tangibles and reliability dimensions showed the largest service gaps. Furthermore, the Customer Satisfaction Index value was 76.47%, which falls within the satisfied category. Nevertheless, improvements in service quality are still required, particularly regarding physical facilities, travel comfort, and departure punctuality.